Interaction of repetition and retention interval influences the transfer effect after answer feedback for episodic memory - Wang, Lingwei; Yang, Jiongjiong (Frontiers in Psychology, 2025)
IntroductionRetrieval practice with answer feedback is an efficient way to enhance episodic memory, but previous studies fail to find a robust transfer of learning for non-trained information. The aim of this study was to clarify the boundary conditions for the transfer effect after answer feedback.MethodsTwo groups of participants learned episodic sentences through single or repeated study and training (ST, SSTT), then they were tested at 10 min, 1 day and 1 week. During the training phase, only half of the items were trained under conditions of feedback, no feedback, or restudy, while the other half items were not trained.ResultsThe transfer effect (i.e., feedback vs. restudy condition for the non-trained items) was influenced by the interaction of repetition and retention interval, as it appeared at 10 min after SSTT but not after ST. Moreover, the transfer effect declined over time, and was significantly lower than chance level at 1 week after SSTT.DiscussionThe results suggest that the transfer effect after answer feedback could be obtained after repeated study and training for the episodic information, but it is short-lived. They also highlight the time change of memory specificity and generalization due to answer feedback.